A Task Analysis Methodology for the Development of Minimum Physical Employment Standards. - Stevenson, Richard D. M.; Siddall, Andrew G.; Turner, Philip F. J.; Bilzon, James L. J. (Journal of Occupational & Environmental Medicine, 2016)
Objective: The aim of this study was to develop a systematic task analysis process for determination of minimum acceptable job performance in arduous safety-related occupations. Methods: A task analysis using modifications on established methods was completed in UK firefighters. Subject-matter experts (all male) identified critical, physically arduous tasks generic to all UK firefighters and developed individual, role-specific task simulations. Video footage and blinded voting were used to determine minimum acceptable task performance. Results: Eight tasks were identified in combination with role-specific variations, task simulations suitable for use in a physical demands analysis, and corresponding minimum acceptable performance. Conclusions: The bespoke steps highlighted here allow structured identification of task-specific minimum performance standards and simulations from which physical employment standards could be based. However, including a more divergent expert panel with respect to age, sex, and race would strengthen the applicability of this framework in future practice.